Quality control methods adopted by food industries (Research, Society and Development, 2023)
Quality management is a mandatory subject in organizations, after all, customers are increasingly demanding and selective. This means that, without an adequate standard, no industry can remain in the market. What contributes to quality management are quality tools, such as Standard Operating Procedure (SOP), Good Manufacturing Practices (GMP), Hazard Analysis and Critical Control Points System (HACCP), ISO 22000, Plan ), Do (Execute), Check (Verify), Act (PDCA), Standard Operational Hygiene Procedure (PPHO), allow you to analyze the entire production process and failures in product quality control. Furthermore, they propose some solutions to avoid possible losses and loss of customers. In the case of food industries, they are linked to the event of a food outbreak for a long time, often not having the chance to continue with their activities, and may suffer financial losses. The objective of this study was to evaluate the quality control methods adopted by the food industries. A narrative bibliographic review was adopted as a methodological strategy. The data collected was grouped and framed to compose the results of this study. The results of this study indicate that most industries make use of quality tools. The minority uses quality tools, but they still have flaws in their execution. Through the results obtained, it was possible to conclude that quality tools help to solve problems efficiently and safely, optimizing production processes and reducing waste.